THE RELATIONSHIP BETWEEN PARENT AND PEER ATTACHMENT, LONELINESS, PERSONALITY, SOCIAL MEDIA, AND TIME SPENT ALONE ON HOBBIES AMONG MALAYSIAN LATE ADOLESCENTS WITH ANXIOUS SELF-PREOCCUPATION - Tan, Terence Cheng Xi; Ng, Joo Hou (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
Background: Social anxiety is prevalent among Malaysian late adolescents. Anxious self-preoccupation (ASP), characterised by heightened self-focused attention in social situations, has been proposed as a cognitive mechanism linking insecure attachment to social anxiety and interpersonal difficulties. However, limited research has examined ASP's relationship with parent and peer attachment and loneliness in the Malaysian context, or the pathways through which these relationships operate. Objective: This study examined whether personality traits, social media usage, and time spent alone on hobbies mediate the associations between ASP and relational outcomes (i.e., parent and peer attachment) as well as loneliness. Methods: A cross-sectional quantitative design was used. 189 Malaysian late adolescents (aged 18–24) completed self-report measures of ASP, parent and peer attachment, loneliness, personality, social media usage, and time spent alone on hobbies. Mediation analyses were conducted using PROCESS Macro with bootstrapped confidence intervals. Results: ASP significantly predicted lower maternal (β = −.33), paternal (β = −.25), peer attachment (β = −.23), and higher loneliness (β = .51). Extraversion and conscientiousness fully mediated the ASP–maternal attachment relationship; extraversion partially mediated the ASP–paternal attachment relationship; and neuroticism partially mediated the ASP–loneliness relationship. None of the tested mediators significantly accounted for the ASP–peer attachment relationship. Social media usage and time spent alone on hobbies did not significantly mediate any of the tested relationships. Conclusion: These findings extend Vertue's (2003) attachment-based model of social anxiety to a Malaysian context, suggesting that ASP-related reductions in extraversion and conscientiousness may impair parental relationship quality, while higher neuroticism levels may increase loneliness risk among Malaysian late adolescents. Practitioners working with socially anxious clients should consider prioritising personality-linked emotion regulation. Future longitudinal research using cross-lagged panel models is recommended to examine the directionality of these relationships.